RANCANGAN ALAT PELEPAS RETAINING BOLT KEYWASHER SEBAGAI ALAT BANTU PELEPASAN GAS GENERATOR TURBINE DISK PADA MOTOR TURBIN PT6A20A DI HANGAR 01 PROGRAM STUDI TEKNIK PESAWAT UDARA - Mario Mabilehi; Ego Widoro; Zulina Kurniawati (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
Special tools for retaining bolt key-washer removal are not available, it cause retaining bolt key-washer cannot be removed at PT6A-20A engine practical, so that need to design these special tools. First step to design retaining bolt key-washer detachment tool as gas generator turbine disk aiding detacher tool for motor turbine PT6A-20A is to define weight, dimension, and force in which the tool is used. Then followed by the calculation and measuring process so that the shape, dimension and material for this tool can be determined. Next the writer start to design based on the available calculation and measurements by using theories related to this particular design. Then followed by the manufacturing of the tool based on the design being made.The tool is manufactured with 24,6 mm of detachment tool diameter and have 7,2 mm of high and 2,2 mm of thick. Protector tool have 38 mm outside diameter and 26 inner diameter. From the result of testing process,the retaining bolt keywasher dettachment tool has successfully removed the retaining bolt keywasher with the moment 78.056,60 N-mm and the protector toll has succesfully to protect hole of gas generator turbine disk shaft with moment 23.416,05 N-mm. And is set to use on cadet’s practice to fulfill motor turbine syllabus due to the unavailability of protective tool on the axle of gas generator turbine disk and retaining bolt key-washer detachment tool on gas generator turbine disk on motor turbine PT6A-20A in Hangar 01 Aircraft Engineering